2022
DOI: 10.1063/5.0075918
|View full text |Cite
|
Sign up to set email alerts
|

3D cellulose fiber networks modified by PEDOT:PSS/graphene nanoplatelets for thermoelectric applications

Abstract: Organic materials have attracted considerable attention for thermoelectric (TE) applications. Given their potential as wearable power generators, there is an urgent need to develop organic TE materials that possess superior electronic properties as well as excellent mechanical and environmental stability. Here, we develop paper-based TE materials using the PEDOT:PSS, graphene nanoplatelets (GNPs), and a starch-based biopolymer as a binder for GNPs. The device fabrication consists of spraying the biopolymer/GNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…According to literature, the particles and elongated features represent the conducting parts and insulating domains of PEDOT:PSS, respectively. [ 18–20 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to literature, the particles and elongated features represent the conducting parts and insulating domains of PEDOT:PSS, respectively. [ 18–20 ]…”
Section: Resultsmentioning
confidence: 99%
“…According to literature, the particles and elongated features represent the conducting parts and insulating domains of PEDOT:PSS, respectively. [18][19][20] Simple vertical supercapacitor structures are composed of the ion gel between two electrodes of either PEDOT:PSS or AuNWs (Figure 2a). The ability of those electrodes to store charges is investigated by the cyclic voltammetry (CV) and galvanic charge-discharge (GCD) techniques (Figure S2, Supporting Information).…”
Section: Supercapacitor Electrodes and Electrolytesmentioning
confidence: 99%
“…147 Cotton and cellulose have been used as a host for active materials with mixed results. [147][148][149] Cataldi et al have shown that similar fiber-based TEGs can be realized by spray-coating cotton fibers with a mixture of doped nanocarbon species (active material) and aleuritic acid (binder) to produce a biodegradable composite for thermoelectric applications. 147 The proof-of-concept TEG made entirely from the organic textile-based thermocouples yielded a maximum power output of %1.0 nW at DT ¼ 70 K. 147 Spraycoated or solution-soaked thermoelectric fibers also have the benefit of being extremely scalable.…”
Section: Thermoelectric Fibersmentioning
confidence: 99%
“…PEDOT:PSS conductive fibers have relatively high electrical conductivity, , stability, and charge storage, which is why they are used for many high-tech applications, such as smart textiles, , flexible electrodes, , sensors, , and actuators . PEDOT:PSS can be spun into a conductive fiber or filament or can be produced during wet spinning , or electrospinning of fibers …”
Section: Pedot:pss-based Conductive Fibersmentioning
confidence: 99%